Hakikat Tri Kona Dalam Lontar Ganapati Tattwa - Anak Agung Gede Wiraputra (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2022)
In today's life, literary works in the form of lontar still exist as a guide in carrying out religious activities, especially for the Hindu community in Bali. One of the tattwa lontars that became an important work in terms of religious knowledge is the Lontar Ganapati Tattwa. This paper attempts to analyze the nature of the Tri Kona teachings contained in Lontar Ganapati Tattwa with a set of semiotic and religious theories supported by content analysis and descriptive analysis methods. The results of the analysis show that Lontar Ganapati Tattwa is a type of philosophical literary work which contains the essence of secret teachings related to the three omnipotence of God called Tri Kona, namely utpati 'creating', sthiti 'maintaining', and pralina 'melting'. The nature of utpati 'creation' is shown through the description of the process of creating the universe called macro realm/bhuana agung and the micro realm/bhuana alit. The essence of Sthiti 'maintaining' is explained through the description of the meaning of Shiva Linga as a place for the atman to always animate and protect every creature in the universe. The essence of pralina is presented through secret teachings about liberation 'moksa' which is the main life goal of every Hindu religious person. If someone wants to explore the three secret teachings of the Lontar Ganapati Tattwa, it is necessary to clean the heart and purity of the soul and be accompanied by the guidance of a spiritual teacher who always gives advice and advice, so that a complete understanding and perfect implementation will be achieved.